2021
DOI: 10.1186/s13073-021-00828-8
|View full text |Cite
|
Sign up to set email alerts
|

Highly elevated polygenic risk scores are better predictors of myocardial infarction risk early in life than later

Abstract: Background Several polygenic risk scores (PRS) have been developed for cardiovascular risk prediction, but the additive value of including PRS together with conventional risk factors for risk prediction is questionable. This study assesses the clinical utility of including four PRS generated from 194, 46K, 1.5M, and 6M SNPs, along with conventional risk factors, to predict risk of ischemic heart disease (IHD), myocardial infarction (MI), and first MI event on or before age 50 (early MI). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 48 publications
7
35
0
Order By: Relevance
“…One aspect of genetic risk estimation that has not been fully explored is the role of age in modulating the effects of genetic risk. Several studies have shown that the prediction power of PRS varies across age groups in diseases including breast cancer [ 8 ], ischaemic heart disease [ 9 ] and prostate cancer [ 10 ]. Similarly, the standardised incidence ratio of breast cancer for BRCA1/2 mutation carriers also varies with age [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…One aspect of genetic risk estimation that has not been fully explored is the role of age in modulating the effects of genetic risk. Several studies have shown that the prediction power of PRS varies across age groups in diseases including breast cancer [ 8 ], ischaemic heart disease [ 9 ] and prostate cancer [ 10 ]. Similarly, the standardised incidence ratio of breast cancer for BRCA1/2 mutation carriers also varies with age [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, we note that there was an almost significant interactive effect between being a past smoker and the PRS. Since PRS is known to be correlated to certain conventional CAD risk factors [ 10 , 30 ], it is plausible that some fraction of incident CAD risk explained by PRS may be dependent on smoking status. While this paper is not expressly predictive in nature, we note that the addition of PRS may not have provided additional risk discrimination on top of BMI and smoking because by middle age, the genes that compose this risk score may have already exerted their influence, and thus the PRS would not be expected to add discriminatory ability.…”
Section: Discussionmentioning
confidence: 99%
“…Isgut et al. 98 use logistic regression on polygenic risk scores to improve myocardial infarction risk prediction. Zhou et al.…”
Section: Machine Learning For Genomics In Target Discoverymentioning
confidence: 99%
“…Paré et al 97 use gradient boosted regression to approximate polygenic risk score for complex traits such as diabetes, height, and body mass index. Isgut et al 98 use logistic regression on polygenic risk scores to improve myocardial infarction risk prediction. Zhou et al 99 apply DNNs on the epigenomic features of both the coding and non-coding regions to predict gene expression for more than 200 tissue and cell types and later identify disease-causing SNPs.…”
Section: Variant Callingmentioning
confidence: 99%